A comparison of shear‐mixing and solvent‐induced on phase behavior, thermal and dielectric properties of PVDF‐HFP/MOF composites. Issue 32 (15th June 2022) - Paramee, Samanya; Guo, Ruyan; Bhalla, Amar S.; Manuspiya, Hathaikarn
Abstract: The effects of processing techniques significantly alter on the electroactive β‐phase, thermal, and dielectric behavior of polymer composites. The metal–organic framework filler (C3 N2 H5 )(Mg(HCOO)3 ), HImMg is prepared and introduced into poly(vinylidenefluoride‐co‐hexafluoropropylene) (PVDF‐HFP) matrix using two distinguished methods: melt‐mixing and solution‐casting methods. The processing conditions are important in determining the dominant phase in PVDF‐HFP. As a result of solvent‐induced crystallization, the β‐phase content of solution‐cast composites containing 10% HImMg is 22% higher than that of melt‐mixed composites. In both methods, the nucleating effect of HImMg particles increases the overall crystallinity of the polymer matrix and enhances the dielectric constant in composite films by improving the interfacial and dipolar polarization. Furthermore, the melt‐mixed composites with 7 wt% HImMg demonstrate the highest dielectric constant of 17.8 at 1 kHz, showing an enhancement of 59% compared with that of pristine PVDF‐HFP. Meanwhile, the dielectric loss is suppressed at 0.083. These findings suggest the possibility of enhancing composites' electroactive phase and dielectric properties without mechanical stretching or a large electrical field. Abstract : Solvent‐induced crystallization enhances the electroactive β‐phase in a solution‐casting rather than in a melt‐mixing one. The incorporation of HImMg improves the interfacial interaction between negatively charge of the PVDF‐HFP and positively charged of imidazolium groups, relating to increase the crystallinity of the PVDF‐HFP matrix and the dielectric constant by increasing the interfacial and dipolar polarization in both techniques.